The Effect of Physical Activity Intervention on the Well-Being of Pregnant Women: Literature Review - Tetti Solehati; Afni Faddilah Taslam; Nezla Puspita; Ima Rismawati; Dinyatul Arba Ramdhona; Khalishah Salsabila; Lu'lu Nadiyya Samdjaya; Yuliana Sri Rahayu; Cecep Eli Kosasih (Indonesian Journal of Global Health Research, 2025)
Physical activity during pregnancy needs to be considered because it will have a positive impact in reducing medical interventions during childbirth, such as: amniocentesis, labor induction, and the risk of cesarean section. Low physical activity in pregnant women causes adverse effects, such as: excess weight during pregnancy, diabetes, and hypertension. This study aimed to identify physical exercise that is effective in improving the welfare of pregnant women. Literature review research design. Literature search assisted by Pubmed, Science Direct, and Ebsco databases using the keywords "Pregnant women" OR "Pregnancy" OR "Pregnant" AND "Exercise" OR "Exercises" OR "Physical Activity" AND "Well-being" OR "Life satisfaction" OR "Life quality" by considering the inclusion criteria including: fultex on physical exercise interventions in pregnant women published from 2014-2024, in English, primary research with Randomized Controlled Trial, Clinical Trial, quasi-experiment designs.This study found 10 articles that met the requirements for analysis, which were then analyzed using JBI. The results of the study found six themes of the influence of physical activity during pregnancy on the welfare of pregnant women, namely: improving sleep quality and maternal-fetal attachment, reducing pain during pregnancy, affecting labor, improving fetal well-being and intrauterine safety, optimal weight gain, and preventing postpartum depression. Based on the results of the study, it was concluded that there are various types of physical exercise in improving maternal well-being during pregnancy, so it is recommended that pregnant women do physical activity during their pregnancy to improve the well-being of the mother and her fetus.